Tung (Aleurites fordii) Avaliação do potencial energético do fruto e do biodiesel - Zornitta, Nelson (2014)
The oil produced by the Tung s fruit (Aleurites fordii) is already inserted in the market due to its numerous applications that comprehends drying qualities reaching the packing production. In this study, it was evaluated the energetic potential of the Tung s fruit, oil and biodiesel to fill the gap of unpublished information. The fruits were harvested in Cascavel, state of Paraná, Brazil, and they were kept in a shadow place for drying in a period of six months. When the fruits were sliced it was separated the pericarp, the seed coat and the seed. The experiments were performed at the Unioeste campus. The results obtained show that the moisture of crushed seeds presented a value of 3.81% and the seed that was not crushed, 4.5%. The average yielding obtained from the oil extracted from the seeds using the Soxhlet equipment presented a value of 50.6% with a standard deviation of 1.22%; the value of density obtained using the pycnometer was 931.5 g L-1; the value of acid index obtained by titration was 4.5 mg KOH g-1. Biodiesel was produced using the methyl route through a basic catalysis with potassium hydroxide, presenting a density value of 910.8 g L-1 and the specific mass 909.2 kg m-3 at 20 ° C, acid index of 0.473 mg KOH g-1 and flash point of 178 °C. The energetic potential of the Tung was evaluated by the determination of the higher heating value of the mass, oil and biodiesel and from the development of the specific Tung s biodiesel consumption and its blends with diesel. The heating values obtained using a Combustion Calorimeter, e2k, are presented as follow: 9209 kcal kg-1 for the extracted oil; 9117 kcal kg-1 for the commercial oil; 9149 kcal kg-1 for the biodiesel; 7017 kcal kg-1 for the crushed seed; 4840 kcal kg-1 for the pie after extraction; 4608 kcal kg-1 for the pericarp; and 3592 kcal kg-1 for the seed coat. The value of the heating value for the entire dry fruit was estimated through by calculation and the value obtained was 4818 kcal kg-1. The values of ash level are shown as follow: 1.80% for the crushed seed; 2.24% for the pie after extraction of oil; 0.66% for the pericarp; and 5.80% for the seed coat. The results obtained confirms the high level of oil in the Tung s seeds; moreover, the biomass of the Tung s fruits in natura show considerable values for the heating value (LHV > 1850 kcal kg-1) and when it is put together to the low level of ash (< 8%) the Tung seed can be considered a renewable source of clean energy